2010
DOI: 10.1007/s00246-010-9863-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Posterolateral Thoracotomy and Video-Assisted Thoracoscopic Clipping for the Treatment of Patent Ductus Arteriosus in Neonates and Infants

Abstract: This study was designed to compare the long-term clinical outcomes and costs between video-assisted thoracic surgery (VATS) and posterolateral thoracotomy (PT) in neonates and infants. This study enrolled 302 patients with isolated patent ductus arteriosus (PDA) from January 2002 to 2007 and followed them up until April 2010. A total of 134 patients underwent total VATS (VATS group), and 168 underwent PDA closure through PT (PT group). The two groups were compared according to clinical outcomes and costs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 20 publications
2
21
0
1
Order By: Relevance
“…No patients required reintervention, but VATS had fewer complications, a lower cost, a shorter LOS, and a shorter time in the operating room . 32 Th e same authors also compared the outcomes of pediatric and adult PDAs treated either by VATS or by catheter-based therapy using the Amplatzer occluder and found that subjects undergoing VATS did not require reintervention compared with 4.1% in the catheter arm. VATS also had fewer complications and a lower cost but an increased duration of procedure and a longer LOS.…”
Section: Discussionmentioning
confidence: 99%
“…No patients required reintervention, but VATS had fewer complications, a lower cost, a shorter LOS, and a shorter time in the operating room . 32 Th e same authors also compared the outcomes of pediatric and adult PDAs treated either by VATS or by catheter-based therapy using the Amplatzer occluder and found that subjects undergoing VATS did not require reintervention compared with 4.1% in the catheter arm. VATS also had fewer complications and a lower cost but an increased duration of procedure and a longer LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Видеоторакоскопия используется для лигирования открытого артериального протока. В последнее вре-мя пока только в западной печати появились работы по ее использованию для протезирования клапанов сердца [40][41][42][43][44].…”
Section: Introductionunclassified
“…[2][3][4] In addition, comparison studies of thoracoscopy versus thoracotomy have thus far demonstrated no significant global differences in safety and efficacy. [5][6][7][8][9] Nevertheless, the data comparing the two methods remain sparse and conflicted on multiple important technical indices. Some studies have indicated that thoracoscopic surgery is associated with shorter hospital stays 6,8 , reduced operative times 6,7 , and fewer post-operative complications 7,9 , while others have described either neutral or opposing findings.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Nevertheless, the data comparing the two methods remain sparse and conflicted on multiple important technical indices. Some studies have indicated that thoracoscopic surgery is associated with shorter hospital stays 6,8 , reduced operative times 6,7 , and fewer post-operative complications 7,9 , while others have described either neutral or opposing findings. 6,7,9 Some studies have also focused entirely on neonate and infant patient populations, for which outcomes may be confounded by co-morbidities or clinical status requiring urgent ductus closure, or have included predominantly low-birth-weight infants.…”
mentioning
confidence: 99%